ANALISIS BENTUK MUSIK DAN MAKNA LIRIK LAGU “GOODNESS OF GOD” KARYA JENN JOHNSON DAN BETHEL MUSIC - Kharis Noel Batuara; Dwi Sutrianto (JURNAL PENABIBLOS, 2024)
This article delves into the intricate interplay between music and lyrical meaning in the song "Goodness of God." Grounded in the exploration of both musical and semantic elements, the study aims to unravel the artistic and emotional dimensions that contribute to the overall expression of beauty and the communication of God's Goodness. The analysis of the musical component encompasses a scrutiny of the melody's structure, rhythmical patterns, instrumental choices, and vocal techniques. Each element is examined for its contribution to the emotive and aesthetic qualities of the music. Concurrently, the examination of lyrical meaning involves a thematic interpretation and an exploration of denotative and connotative meanings within the lyrics.Furthermore, the research addresses the integration of music and lyrics, investigating how these elements harmonize to reinforce the message of God's Goodness. The artistic cohesion between the two facets is evaluated for its ability to create a harmonious and profound experience for the listener. In conclusion, the findings of this analysis not only offer insights into the specific artistic components of the song "Goodness of God" but also shed light on the broader connection between music and spirituality. This research contributes to the understanding of how musical expression and lyrical depth collaboratively convey the profound message of God's benevolence.